2012
DOI: 10.1590/s0036-46652012000100005
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1-mother-to-child transmission and associated characteristics in a public maternity unit in Presidente Prudente, Brazil

Abstract: SUMMARYIn children, vertical transmission is the main form of HIV infection. Our aim was to determine the prevalence of HIV-1 vertical transmission in mother-infant pairs in a public maternity ward in Presidente Prudente, SP. Additionally; we sought to identify characteristics associated with this form of transmission. The files of 86 HIV-1-infected mothers and their newborns referred to a Public Hospital from March 2002 to March 2007 were analyzed. The HIV-1-RNA viral load of the newborns was determined by bD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
3
0
2
Order By: Relevance
“…Regarding TV cases, it was observed they all occurred with some factor associated with increased transmission (syphilis, without prenatal and without art). This rate is similar to that found in another location study (7) and in other Brazilian cities (10,15,29) , however was fewer than the Brazilian rate in 2001 (7.1%) and less than the rate of TV in the Southeast (7.0 %) (30) . In Brazil, the rates of HIV mother-to-child transmission had decreased in the last decade due implementation of the measures of the STD/Aids program (6) .…”
Section: Discussionsupporting
confidence: 89%
“…Regarding TV cases, it was observed they all occurred with some factor associated with increased transmission (syphilis, without prenatal and without art). This rate is similar to that found in another location study (7) and in other Brazilian cities (10,15,29) , however was fewer than the Brazilian rate in 2001 (7.1%) and less than the rate of TV in the Southeast (7.0 %) (30) . In Brazil, the rates of HIV mother-to-child transmission had decreased in the last decade due implementation of the measures of the STD/Aids program (6) .…”
Section: Discussionsupporting
confidence: 89%
“…1 Among them, it is observed that the proportion of HIV-infected women grows quickly. 2 This fact leads to an important point: HIV infection in pregnant women. This is because, in addition to HIV be transmitted by the exchange of bodily fluids such as blood, vaginal secretions and semen, the infection can also occur in HIV-positive mothers to their babies during pregnancy, childbirth or breastfeeding, and this type of transmission It gives the name of vertical transmission.…”
mentioning
confidence: 99%
“…[4][5] A given relevant in this context is that, according to estimates, there are about 240.000 women age reproductive who have the AIDS virus and that most do not know it was HIV-positive. 5 In Brazil, the HIV case detection rate in pregnant women in 2012 amounted to 2,4 cases per 1000 living born. 4 In a pregnant woman, when there is no type of treatment, the rate of vertical transmission of HIV to the baby can be of 20%.…”
mentioning
confidence: 99%
“…Entre as formas de contaminação pelo HIV está o leite materno, sendo a principal fonte de infecção do vírus em crianças (4) . Isso justifica a recomendação de proibir a amamentação cruzada, ou seja, a prática de oferecer o leite materno diretamente da mama ou ordenhado a uma criança que não o seu próprio filho (5) pela Organização Mundial da Saúde (OMS), Fundo das Nações Unidas para a Infância (UNICEF) e adotada pelo Ministério da Saúde do Brasil.…”
unclassified